SINGULARITAS JUMLAHAN SOLUSI FUNDAMENTAL PERSAMAAN DIFUSI DALAM PEMODELAN TRANSFER MASSA - Cahyono, Edi; Kartono, Kartono (MATEMATIKA, 2006)
This paper discusses the sum of fundamental solutions of 2-D diffusion equation (for constant diffusion rate). Although a linear diffusion equation is considered, the sum of fundamental solutions is not automatically a solution. This is because of the presence of a singularity at the origin O. In this paper, it will be shown that the sum of fundamental solutions is a solution of the primitive of diffusion equation, diffusion equation in an integral form. It is also shown that the sum of fundamental solutions represents mass tranfer process caused by a source that impulsively releases Â some amount of mass.